An Indigenous critique: Expanding sociology and recognizing unique Indigenous knowledge - Mackay, Ried E (Frontiers in Sociology, 2022)
This essay suggests that sociologists should integrate into their critical research work on North America an Indigenous critique/method based on Indigenous knowledge. As an Indigenous scholar myself I have been frustrated by the lack of frameworks based on Indigenous knowledge rather than merely referencing that knowledge. Strong foundations of ancient Indigenous thought and philosophical tradition— which often differs dramatically from Western traditions—is explored through three concepts: Ch’ixi, the Indigenous pragmatic, and Mexica concepts of Truth. Arguments and controversy for accepting the validity of Indigenous sources are also addressed. The paper concludes with discussions of specific empirical questions and puzzles related to already familiar concepts and analyses such as systemic racism theory, multi-raciality, religion, and postcolonial theory.